The Impact of Organisational Culture on Innovation in Nepalese Star Hotels: The Mediating Effect of Strategic Leadership - Subedi, Dhruba Prasad; Bhandari, Dilli Ram (Journal of Business and Social Sciences Research, 2024)
Organisational culture drives innovation by cultivating values, behaviours, and mindsets that encourage creativity, collaboration, and risk-taking, thereby enhancing the organisation’s ability to generate and implement new ideas. Strategic leadership strengthens this relationship by aligning cultural values with innovation objectives, empowering teams, and guiding organisations towards embracing change and creative solutions. This study aims to examine the impact of strategic leadership on the relationship between organisational culture and innovation in three-star hotels located in Kathmandu. To achieve this objective, data were collected from 272 managerial, assistant, officer, and junior-level employees using a structured questionnaire administered through a convenience sampling method. Data analysis was conducted using Process Macro 4, applying a 95% confidence interval and 5,000 bootstrapping samples. This study reveals that organizational culture enhances innovation by creating a supportive environment that promotes creativity, collaboration, and openness to embracing new ideas and approaches among the employees. This study also highlighted the vital role of strategic leadership in bridging organisational culture with innovation.